VILLAGE CAPACITY BUILDING STRATEGY IN EFFORTS TO PREVENT STUNTING IN PANDEGLANG - Candarmaweni Lawaceng; Amy Yayuk Sri Rahayu (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
Local autonomy that revolves in Indonesia has provided opportunities for villages to develop independent villages in accordance with the potential of the villages —in line with the Undang-Undang Nomor 6 Tahun 2014 concerning Villages. The most common health problem in the rural areas and directly related to the quality of Indonesian human resources is stunting. For this reason, this study is intended to illustrate how the strategy of increasing the capacity of organizations and increasing the capacity of village officials in efforts to prevent stunting in villages. Besides the government, stunting prevention in Pandeglang also involves the private sector and academics. These sectors are directly involved in increasing village capacity to prevent stunting. This study used a qualitative approach with descriptive method. Data collection techniques were in-depth interviews, observation, and study of documents related to the research topic. From the results of the study it was found that the ability of organizations in planning, implementing, and evaluating programs, managing village funds, socialization and communication, partnerships, fostering village government and village communities, became the dominant factor in handling stunting in Pandeglang.